Resting-state electroencephalographic correlates of cognitive reserve: Moderating the age-related worsening in cognitive function - Buján, Ana; Sampaio, Adriana; Pinal, Diego (Frontiers in Aging Neuroscience, 2022)
The present exploratory study aimed to investigate the resting-state electroencephalographic (rsEEG) correlates of cognitive reserve from a lifespan perspective. To this aim, current source density (CSD) and lagged-linear connectivity (LLC) measures were assessed. We firstly explored the relationship between rsEEG measures for the different frequency bands and a socio-behavioral proxy of cognitive reserve, the Cognitive Reserve Index (CRI). Secondly, we applied moderation analyses to assess if any of the correlated rsEEG measures showed a moderating role on the relationship between age and cognitive function. Moderate negative correlations were found between the CRI and occipital CSD of delta and beta 2. Moreover, inter and intra-hemispheric LLC measures were correlated with the CRI, showing a negative association with delta, and positive associations with alpha 1, beta 1 and beta 2. Among those correlated measures, just two rsEEG variables were significant moderators of the relationship between age and cognition: occipital delta CSD and right hemispheric beta 2 LLC between occipital and limbic regions. The effect of age on cognitive performance was stronger for higher values of both measures. Therefore, lower values of occipital delta CSD and lower beta 2 LLC between right occipital and limbic regions might protect or compensate for the effects of age on cognition. Results of this exploratory study might be useful to allocate more preventive efforts to curb the progression of cognitive decline on those adults with less CR, possibly characterized by these rsEEG parameters at a neural level. However, given the exploratory nature of the present study, more conclusive work on these rsEEG measures is needed to firmly establish their role on the cognition-age relationship, as for example verifying if these measures moderate the relationship between brain structure and cognition.